Persistent Trigeminal Artery and Dural Arteriovenous Fistula: A Case Report - El Hajj, Gabriella Alves Villatoro; Vieira, Raphael Vinícius Gonzaga; Ribeiro, Isabela Costa; Delcole, Giovanna; Aguiar, Paulo Henrique Pires (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
The persistent trigeminal artery is a carotid-vertebrobasilar anastomosis, mostly unilateral. Embryonic arteries typically disappear during prenatal development, but in rare instances, they may persist. The prevalence of this anastomosis in adulthood is 0.4% in individuals without vascular abnormalities.A 41-year-old female patient sought emergency care with complaints of neck pain associated with a headache, starting one month ago, and worsening associated with paresthesia in the left upper limb. The magnetic resonance angiography of the skull revealed a left sigmoid sinus dural arteriovenous fistula (dAVF), irrigated by the left middle meningeal and ipsilateral occipital arteries. The same examination revealed the presence of a persistent trigeminal artery originating from the cavernous segment of the right internal carotid artery.The persistent trigeminal artery is associated with other arteriovenous abnormalities. The most common symptom is trigeminal neuralgia. Complications may result from aneurysm ruptures, and the treatment of the condition still depends on the associated clinical presentations.The persistent trigeminal artery is a rare incidental finding in medical practice, as are studies related to the topic. Recognizing this abnormality in affected patients is essential, as there have been reports of complications related to the finding, especially before surgical procedures. Therefore, there is a need to expand the literature data on the persistent trigeminal artery and its appropriate management.
Keywords: persistent trigeminal artery; remnant trigeminal artery; persistent embryonic arteries; dural arteriovenous fistula; neurovascular malformation; cerebral angiography